Model Pembelajaran Kooperatif Tipe Numbered Head Together sebagai Upaya Meningkatkan Prestasi Belajar Prakarya - Sri Rejeki (JURNAL PENDIDIKAN, 2021)
This study aims to improve learning achievement of craft subjects through cooperative learning model type NHT in students of class VII G SMP Negeri 5 Sukoharjo first semester academic year 2017/ 2018.This research is a Classroom Action Research conducted in class VII G SMP Negeri 5 Sukoharjo first semester of academic year 2017/ 2018 with 32 students. Data collection techniques used are tests, observations, and documentation. The stages of data analysis in this study are data collection, data reduction, data presentation, and conclusion. The success indicator is the average score of the student's test at least 80.0 and many students with a value above the minimum mastery criteria (KKM) of 70.0 reach ≥ 85%.Based on the research that has been done, it can be concluded that the application of cooperative learning model type NHT can improve learning achievement of craft subjects student of class VII G SMP Negeri 5 Sukoharjo. Before the action / pre cycle, student learning outcomes reaching KKM 15 students or 46,9%, in cycle I, 23 students or 71,9% and in cycle II, 30 students or 93,75%. The average value of the class before the action / pre cycle was 68.5 after the first cycle action was 76,7 and after the second cycle action was 82.1.Keywords: Cooperative learning model type NHT, learning achievement of craft subjects. AbstrakPenelitian ini bertujuan untuk meningkatkan prestasi belajar prakarya melalui model pembelajaran kooperatif tipe NHT pada siswa kelas VII G SMP Negeri 5 Sukoharjo semester I tahun pelajaran 2017/ 2018. Penelitian ini adalah Penelitian Tindakan Kelas yang dilakukan di kelas VII G SMP Negeri 5 Sukoharjo semester I tahun pelajaran 2017/ 2018 yang berjumah 32 siswa. Teknik pengumpulan data yang digunakan adalah tes, observasi, dan dokumentasi.Tahap-tahap analisis data dalam penelitian ini adalah pengumpulan data, reduksi data, penyajian data, dan penarikan kesimpulan. Indikator keberhasilan adalah nilai rata-rata tes siswa sekurang-kurangnya 80,0 dan banyak siswa dengan nilai di atas kriteria ketuntasan minimal (KKM) yaitu 70,0 mencapai ≥ 85%. Berdasarkan penelitian yang telah dilakukan, dapat disimpulkan bahwa penerapan model pembelajaran kooperatif tipe NHT dapat meningkatkan prestasi belajar bahasa prakarya siswa kelas VII G SMP Negeri 5 Sukoharjo. Sebelum tindakan/ prasiklus, prestasi belajar siswa yang mencapai KKM 15 siswa atau 46,9%, pada siklus I, 23 siawa atau 71,9% dan pada siklus II, 30 siswa atau 93,75%. Nilai rata-rata kelas sebelum tindakan/prasiklus sebesar 68,5 setelah tindakan siklus I sebesar 71,9 dan setelah tindakan siklus II sebesar 82,1.Kata Kunci: Model pembelajaran kooperatif tipe NHT, prestasi belajar prakarya.